Simulator String yang Diterima Finite State Automata (FSA) Berbasis Android - Azizah Azizah; Fauziah Fauziah (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2019)
Automata is an abstract machine that can recognize (recognize), accept (accept), or generate a sentence in a particular language. There are two types of Deterministic Finite Automata (DFA) and Non-deterministic Finite Automata (NFA). Simulator Finite State Automata is a device that can be used to check the string input in Finite State Automata. The way the simulator works still does not know much about it, through the simulator it is hoped that users are more aware of it.